Enhancing saltiness perception using chitin nanofibers when curing tilapia fillets. (December 2017) - Hsueh, Chih-Yuan; Tsai, Min-Lang; Liu, Tristan
Abstract: This study applied an ultrasonication method to prepare chitin nanofibers (CNFs) with a mean diameter of 111.6 nm, which were then used in a curing solution to increase the saltiness perception of cured tilapia fillets. Subsequently, various concentrations of citric, malic, or lactic acid were used to further enhance the fillets' perceived saltiness. The fillets cured with 0.12–0.18 g/L CNFs had significantly higher saltiness perception scores than the fillets cured with the control solution. The optimal perceived saltiness occurred when the 0.15 g/L group (CNF15) solution was added. In addition, the astringency perception of each fillet group differed insignificantly from the control. When CNF15 was prepared in 40 g/L NaCl curing solution, the addition of 3 g/L citric acid or 4 g/L malic acid, significantly increased the saltiness perception of the fillet and the tasters did not perceive any additional sourness. In contrast, further increasing the lactic acid concentration decreased the perceived saltiness of the fillet. Overall, in specific concentrations, CNFs can increase the saltiness perception of cured fish fillets. Perceived saltiness can be further enhanced by adding adequate amounts of citric or malic acid. Highlights: Saltiness of cured tilapia fillets can be raised by 0.12–0.18 g/L chitin nanofibers. Perceived saltiness of cured fish fillets in 0.15 g/L chitin nanofibers are optimum. Fillets cured in chitin nanofibers and malic acid, saltiness can be further lifted. Fillets cured in chitin nanofibers and citric acid, saltiness can be further lifted.